EFFECT OF SELENIUM CITRATE ON THE GLUTATHIONE STATUS AND THYROID HORMONES IN RATS WITH EXPERIMENTALLY INDUCED HYPOTHYROIDISM - O.O. Sushko; R.JA. Iskra (Biotechnologia Acta, 2025)
Aim. The research purposed to determine the effects of selenium citrate on the characteristics of the antioxidant system and hormone levels in the blood of rats with experimentally induced hypothyroidism.